AN ANTHROPOLOGICAL LOOK AT CULTURAL TOURISM AT PUCLLANA SITE MUSEUM - PAZ FLORES, Gladys (2023)
Tourism produces significant cultural changes that imply a relationship between different socio-cultural groups. In this sense, the enhancement of cultural resources has also diversified tourism products, segmenting the market into “Cultural Tourism”, which includes museums, archaeological sites, art galleries and also visits to indigenous communities. This anthropological study on this segment is fundamental to recognize the cultural aspects and symbols, reciprocal relations between groups and the behavior of actors in these spaces. In this sense, it allows us to identify theoretical concepts and forms of interculturality, identity and roles of both actors taking as their axis the analysis of cultural partner relationships, population flows and symbolic expressions in the interaction between tourists and hosts in spaces where our cultural wealth is exposed, like the Pucllana Museum.